2022
DOI: 10.1002/pc.26877
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multiwalled carbon nanotube on progressive damage of epoxy/carbon fiber reinforced structural composite

Abstract: The present work aims to demonstrate the effect of multiwalled carbon nanotube (MWCNT) on mechanical behavior and damage of woven carbon fiber/epoxy composites through experimental characterizations and multi-scale modeling. Tensile tests were conducted for MWCNT/epoxy nanocomposites, and carbon nanotube (CNT) reinforced laminated open hole composites with different MWCNT weight ratios. The tensile modulus in CNT/epoxy nanocomposite was enhanced by 15.0%, 37.86%, and 22.86% for MWCNT reinforcement of 0.5%, 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Soliman et al [ 15 ] explored the low‐velocity impact response of functionalized‐CNTs/carbon fibers/EP composite and reported that the CNTs addition increased the absorbed energy. The positive effect of MWCNTs on the tensile response of carbon fiber‐EP composites was also shown by Bhowmik et al [ 18 ]…”
Section: Introductionsupporting
confidence: 60%
“…Soliman et al [ 15 ] explored the low‐velocity impact response of functionalized‐CNTs/carbon fibers/EP composite and reported that the CNTs addition increased the absorbed energy. The positive effect of MWCNTs on the tensile response of carbon fiber‐EP composites was also shown by Bhowmik et al [ 18 ]…”
Section: Introductionsupporting
confidence: 60%
“…[10][11][12][13] The addition of 1 wt% CNTs can increase the matrix's electrical conductivity by up to 10 orders of magnitude. [14,15] Introducing dispersed CNTs is known to enhance not only the strength [16,17] and stiffness of composites [18,19] but also their fracture toughness. [20][21][22] However, the formation of local agglomerations of CNTs bundles during resin impregnation process is likely to create singularities and decrease the mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of thermoplastic resins, polyamide 6 (PA6) is frequently selected as matrix resin for manufacturing CFRTP due to its high‐impact resistance, processability, recyclability, and low cost. [ 1 ] It is generally recognized that the interfacial properties not only determine comprehensive mechanical properties, [ 2–4 ] but also affect moisture absorption, [ 5 ] aging resistance [ 6 ] and fracture behavior [ 7 ] of the composites. However, the epoxy‐based sizing on the as‐received carbon fibers (CFs) is designed for thermosetting matrix resin, [ 8 ] which may undergo thermal degradation at the processing temperature of CFRTP [ 9,10 ] and presents weak compatibility with thermoplastic matrix resin.…”
Section: Introductionmentioning
confidence: 99%